Autoestima y su influencia en el comportamiento depresivo en una niña de padres separados - Triviño Yepez, Eddy Alberto (2020)
The present case study is to determine self-esteem and its influence on depressive behavior in a girl of separated parents whose age is 11 years and who is studying the seventh year of basic education in the Juan Montalvo Del Cantón Baba Educational Unit In the Province of Los Ríos, scientific research was applied to obtain the information, as well as basic psychological instruments and techniques in order to reach a presumptive psychodiagnostic in order to propose a solution based on the application of cognitive behavioral psychotherapy, in addition to providing Information to parents about the importance of consolidating good self-esteem since childhood.